2012
DOI: 10.1111/gcb.12032
|View full text |Cite
|
Sign up to set email alerts
|

Global change effects on Bromus tectorum L. (Poaceae) at its high‐elevation range margin

Abstract: Global change is likely to affect invasive species distribution, especially at range margins. In the eastern Sierra Nevada, California, USA, the invasive annual grass, Bromus tectorum, is patchily distributed and its impacts have been minimal compared with other areas of the Intermountain West. We used a series of in situ field manipulations to determine how B. tectorum might respond to changing climatic conditions and increased nitrogen deposition at the high-elevation edge of its invaded range. Over 3 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…Consistent with this interpretation, a recent study carried out at high elevations found that the effect of snow on cheatgrass is neutral (Concilio et al, 2013). An earlier study from the same site showed that snow cover had both negative and positive effects on cheatgrass (Griffith and Loik, 2010).…”
Section: H2) Loss Of Snow Will Contribute To the Effect Of Warmingmentioning
confidence: 72%
“…Consistent with this interpretation, a recent study carried out at high elevations found that the effect of snow on cheatgrass is neutral (Concilio et al, 2013). An earlier study from the same site showed that snow cover had both negative and positive effects on cheatgrass (Griffith and Loik, 2010).…”
Section: H2) Loss Of Snow Will Contribute To the Effect Of Warmingmentioning
confidence: 72%
“…The strong effect of warming on fecundity may reflect the fact that moisture was above average during our experiment and temperature was far from cheatgrass' upper tolerance. First, we expect soil moisture to favor cheatgrass seed production, because this species is extremely responsive to moisture availability (e. g. Hull and Pechanec 1947, Bradley and Mustard 2005, Concilio et al 2013. Second, a separate experiment carried out at the mid elevation site in 2011 provides evidence that temperatures were far from cheatgrass' upper tolerance.…”
Section: Effects Of Warmingmentioning
confidence: 99%
“…In the Intermountain West, soil resources, aboveground productivity and biomass increase with elevation , which might increase competitive pressure from perennial natives (Grime 1979). If warmer temperatures have a positive direct effect on cheatgrass, strong competition might be especially important for limiting cheatgrass performance through negative indirect effects (Suttle et al 2007, Concilio et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive populations are mostly likely to have come from sources in Western and Central Europe, and have invaded huge areas in the Intermountain West (Knapp 1996;Novak and Mack 2001). Of recent concern is the ability of B. tectorum to invade into higher elevation sites such as those at the edge of the western Great Basin and eastern Sierra Nevada (Concilio et al 2013;Leger et al 2009;Griffith and Loik 2010). Given this, what is the potential role of phenotypic plasticity in the ability of B. tectorum to invade semi-arid shrub-steppe A.…”
mentioning
confidence: 99%